Preparation method and application of high-temperature-resistant pressure-sensitive adhesive
By using montmorillonite loaded with magnesium chloride in pressure-sensitive adhesives to promote cross-linking reactions, forming a cross-linking network with a layered structure, the problem of insufficient performance of traditional pressure-sensitive adhesives with high temperature resistance and electrolyte resistance is solved, and a higher level of performance is achieved. High temperature resistance and swelling resistance.
Patent Information
- Application Number
- CN202411261442.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-02-07
AI Technical Summary
The high-temperature resistance and electrolyte resistance of traditional acrylate pressure-sensitive adhesives are insufficient, and cannot be used for a long time in high-temperature environments, and they are prone to swelling and lose their viscosity after soaking in the electrolyte.
By adding montmorillonite loaded with magnesium chloride to the pressure-sensitive adhesive, the cross-linking reaction of monomers around montmorillonite is promoted to form a cross-linking network with a layered structure, thereby improving the high temperature resistance and cohesion of the pressure-sensitive adhesive.
It significantly improves the high temperature resistance and cohesion of the pressure-sensitive adhesive, enhances its stability and electrolyte resistance in high-temperature environments, and avoids swelling.
Smart Images

Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of pressure-sensitive adhesives, and in particular to a preparation method and application of a high-temperature resistant pressure-sensitive adhesive. Background Art
[0002] Solvent-based acrylic pressure-sensitive adhesives are mainly made of solvents and are polymerized by free radicals from soft monomers, hard monomers and functional monomers. Soft monomers refer to monomers with a low homopolymer glass transition temperature. They generally account for more than 60% of the raw monomer dosage of pressure-sensitive adhesives. Their main function is to improve the initial viscosity and adhesion of pressure-sensitive adhesives. The lower the glass transition temperature of PSA, the greater the initial viscosity of the pressure-sensitive adhesive, but it will cause the cohesion of the pressure-sensitive adhesive to decrease. Currently, commonly used soft monomers mainly include: butyl acrylate (BA), isooctyl acrylate (2-EHA), ethyl acrylate (EA), etc. Hard monomers refer to monomers with a high homopolymer glass transition temperature. They not only have a high glass transition temperature but also can improve the tensile strength and hardness of the copolymer. In pressure-sensitive adhesives, they can improve the cohesive strength of the adhesive layer, but they will reduce the interfacial adhesion of the pressure-sensitive adhesive. Currently, commonly used hard monomers mainly include: methyl acrylate (MA), vinyl acetate (VAc), styrene (St), acrylamide (AM), acrylonitrile (AN), methyl methacrylate (MMA), etc. Functional monomers refer to monomers that can copolymerize with soft and hard monomers and have active groups. Their main function is to improve the special properties of pressure-sensitive adhesives, such as anti-pollution, water resistance, solvent resistance, gloss and color retention, etc. The amount of functional monomers used is generally small, usually accounting for 2% to 10% of the total monomers. Currently, commonly used functional monomers include acrylic acid (AA), hydroxyethyl acrylate (HEA), N-hydroxymethyl acrylamide (N-MAM), itaconic acid, maleic anhydride, etc.
[0003] With the development of the new energy vehicle industry, the high temperature resistance of traditional acrylic pressure-sensitive adhesives is poor. The cross-linked acrylic pressure-sensitive adhesive can only be used for a short period of time in an environment of 150°C. In addition, the electrolyte resistance of traditional acrylic pressure-sensitive adhesives is poor. After soaking in an electrolyte environment for 3 to 4 hours, solvent molecules may penetrate into the polymer network and weaken the intermolecular forces such as the van der Waals force between the polymer molecules in the acrylic pressure-sensitive adhesive, resulting in an increase in the distance between the polymer chains, swelling, and loss of viscosity. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a high-temperature resistant pressure-sensitive adhesive. The present invention adds montmorillonite loaded with magnesium chloride into the pressure-sensitive adhesive to promote the cross-linking reaction of monomers around the magnesium chloride loaded by the montmorillonite to achieve the encirclement of a rigid material, thereby improving the high-temperature resistance and cohesion of the obtained pressure-sensitive adhesive.
[0005] To solve this technical problem, the technical solution of the present invention is: a method for preparing a high temperature resistant pressure sensitive adhesive, comprising the following steps: S1, isooctyl acrylate, butyl acrylate, hydroxyethyl acrylate, vinyl acetate, acrylic acid and montmorillonite loaded with magnesium chloride are uniformly mixed, and then an initiator is added in two batches to perform a cross-linking reaction to obtain a glue solution; The interlayer crosslinking reaction of isooctyl acrylate, butyl acrylate, hydroxyethyl acrylate, vinyl acetate and acrylic acid in montmorillonite; the initiator is AIBN; S2. The glue solution obtained in S1 is adjusted to have a solid content of 30% to 40% using ethyl acetate, a curing agent is added, the adhesive is coated, cured, and attached to PET to obtain a high temperature resistant pressure sensitive adhesive.
[0006] Preferably, the crosslinking in S1 comprises the following steps: S11, after the monomers are evenly mixed, they are mixed with ethyl acetate solvent and transferred to a four-necked flask, half of the total amount of initiator is added and gradually heated to 85°C, and when reflux occurs on the condenser, the reaction is continued for 1 hour; S12, adding the remaining monomers, solvent and 1 / 4 of the total amount of initiator evenly into the reaction system within 2 hours, and then keeping the temperature to react for 1 hour; S13, adding the remaining initiator evenly into the reaction system within 0.5 h, and then keeping the temperature to react for 1.5 h; S14, cooling to obtain glue solution.
[0007] The method for preparing montmorillonite-loaded magnesium chloride preferably comprises the following steps: S221, under nitrogen protection, add anhydrous magnesium chloride and ethanol into the flask, stir at 400r / min, the reaction temperature is 80°C, and react for 1 hour; S222, adding silanized montmorillonite to the flask, and continuing the reaction for 1 hour; S223, epichlorohydrin is added to the reaction system, and the reaction is stopped after 30 to 40 minutes. The mixture is allowed to stand, and the upper liquid is removed. The solid product is washed three times with n-hexane, and dried with nitrogen to obtain magnesium chloride supported by montmorillonite.
[0008] The method of inserting magnesium chloride into the interlayer of montmorillonite is as follows: .
[0009] Preferably, polyvinyl pyrrolidone is further added in step S221, and the mass ratio of polyvinyl pyrrolidone to magnesium chloride is (0.5% to 0.8%): 1. In the present invention, polyvinyl pyrrolidone is added to the ethanol dispersion of montmorillonite to interact with the surface of the particles to form an adsorption film, which can wrap the particles and generate repulsion between the particles, thereby effectively preventing the aggregation and precipitation of the particles and achieving uniform dispersion of the particles.
[0010] The method for preparing silanized montmorillonite preferably comprises the following steps: S211, adding montmorillonite and sodium hexametaphosphate to distilled water for dispersion; S212. Stir γ-aminopropyltriethoxysilane in a H2O / ethanol system at room temperature, add dropwise the montmorillonite suspension dispersed in S211, reflux with stirring for 4 to 6 hours, filter, and bake the filter cake at 120°C for 15 hours to obtain silanized montmorillonite.
[0011] Preferably, the volume ratio of H2O to ethanol in the H2O / ethanol system in S212 is 1:100.
[0012] Preferably, the mass ratio of silanized montmorillonite to anhydrous magnesium chloride is (7 to 10):1.
[0013] Preferably, the mass ratio of epichlorohydrin to magnesium chloride is (2.5 to 3.5):1.
[0014] The raw materials preferably used for the crosslinking reaction include the following substances in parts by mass: 40 to 50 parts of isooctyl acrylate; 18 to 25 parts of butyl acrylate; 4 to 8 parts of hydroxyethyl acrylate; 6 to 12 parts of vinyl acetate; Acrylic acid 4 to 8 parts; 10 to 15 parts of montmorillonite loaded with magnesium chloride; Initiator 0.2 to 0.4 parts.
[0015] The preferred curing temperature is 110°C to 120°C.
[0016] By adopting the above technical solution, the beneficial effects of the present invention are: Compared with the prior art which uses heat-resistant monomers with polar and rigid groups to improve the high temperature resistance of pressure-sensitive adhesives, the present invention uses magnesium chloride intercalated montmorillonite to introduce rigid skeleton montmorillonite while promoting the reaction of cross-linking monomers around layered montmorillonite. As the cross-linking reaction proceeds, the montmorillonite is further intercalated and dispersed in the adhesive solution, and is prepared into a high temperature resistant pressure-sensitive adhesive tape by curing and coating. The high temperature resistance of the pressure-sensitive adhesive is improved while the cohesion of the adhesive layer is effectively improved, and the water resistance and heat resistance are effectively improved. DETAILED DESCRIPTION
[0017] In order to further explain the technical solution of the present invention, the present invention is described in detail below through specific embodiments.
[0018] Example 1 This embodiment discloses a method for preparing a high temperature resistant pressure sensitive adhesive, comprising the following steps: S1, isooctyl acrylate, butyl acrylate, hydroxyethyl acrylate, vinyl acetate, acrylic acid and montmorillonite loaded with magnesium chloride are uniformly mixed, and then an initiator is added in two batches to perform a cross-linking reaction to obtain a glue solution; The interlayer crosslinking reaction of isooctyl acrylate, butyl acrylate, hydroxyethyl acrylate, vinyl acetate and acrylic acid in montmorillonite; the initiator is AIBN; the specific amount of each raw material is shown in Table 1.
[0019] S2. The glue solution obtained in S1 is adjusted to have a solid content of 30% to 40% using ethyl acetate, a curing agent is added, the mixture is coated, and the mixture is cured to obtain a high temperature resistant pressure sensitive adhesive attached to PET.
[0020] The crosslinking in S1 in this embodiment includes the following steps: S11, after the monomers are evenly mixed, they are mixed with ethyl acetate solvent and transferred to a four-necked flask, half of the total amount of initiator is added and gradually heated to 85°C, and when reflux occurs on the condenser, the reaction is continued for 1 hour; S12, adding the remaining monomers, solvent and 1 / 4 of the total amount of initiator evenly into the reaction system within 2 hours, and then keeping the temperature to react for 1 hour; S13, adding the remaining initiator evenly into the reaction system within 0.5 h, and then keeping the temperature to react for 1.5 h; S14, cooling to obtain glue solution.
[0021] The method for preparing montmorillonite preferably loaded with magnesium chloride comprises the following steps: preparing montmorillonite with magnesium chloride loaded between layers; S221, under nitrogen protection, add anhydrous magnesium chloride and ethanol into the flask, stir at 400r / min, the reaction temperature is 80°C, and react for 1 hour; S222, adding silanized montmorillonite to the flask, and continuing the reaction for 1 hour; S223, adding epichlorohydrin to the reaction system, reacting for 30 to 40 minutes, stopping, standing, removing the upper liquid, washing the solid product three times with n-hexane, and drying with nitrogen to obtain magnesium chloride supported by montmorillonite; The method of inserting magnesium chloride into the interlayer of montmorillonite is as follows: .
[0022] In this embodiment, polyvinyl pyrrolidone is further added in step S221, and the mass ratio of polyvinyl pyrrolidone to magnesium chloride is shown in Table 1. In the present invention, polyvinyl pyrrolidone is added to the ethanol dispersion of montmorillonite to interact with the surface of the particles to form an adsorption film, which can wrap the particles and generate repulsion between the particles, thereby effectively preventing the aggregation and precipitation of the particles and achieving uniform dispersion of the particles.
[0023] The method for preparing silanized montmorillonite in this embodiment comprises the following steps: S211, add 100g of sodium montmorillonite and 1g of sodium hexametaphosphate to 1500mL of distilled water, stir and disperse for 2h, and then continue to disperse in a high-speed disperser for 0.5h; S212, 1g γ-aminopropyltriethoxysilane (APMS) was stirred in 10ml H2O / ethanol system at room temperature for 2h, and then dropped into the above dispersed montmorillonite suspension. The mixture was refluxed with stirring for 4h, filtered, and the filter cake was dried at 120℃ for 15h to obtain silanized montmorillonite.
[0024] In this embodiment, the volume ratio of H2O to ethanol in the H2O / ethanol system in S212 is 1:100.
[0025] The mass ratio of silanized montmorillonite to anhydrous magnesium chloride and the mass ratio of epichlorohydrin to magnesium chloride in this embodiment are shown in Table 1.
[0026] In this embodiment, the curing temperature is 110° C. and the curing time is 6 minutes.
[0027] Example 2 The main differences between this embodiment and embodiment 1 are shown in Table 1.
[0028] Example 3 The main differences between this embodiment and embodiment 1 are shown in Table 1.
[0029] Example 4 The main differences between this embodiment and embodiment 1 are shown in Table 1.
[0030] Comparative Example 1 The main difference between this comparative example and Example 2 is that the cross-linking stock solution includes the following components in parts by mass: 45 parts of isooctyl acrylate; Butyl acrylate 22 parts; 4 parts of hydroxyethyl acrylate; 8 parts of vinyl acetate; 6 parts of acrylic acid; 1 part of magnesium chloride; 0.2 parts of initiator.
[0031] The mass ratio of epichlorohydrin to magnesium chloride is 3.0:1.
[0032] Comparative Example 2 The main difference between this comparative example and Example 2 is that the cross-linking stock solution includes the following components in parts by mass: 45 parts of isooctyl acrylate; Butyl acrylate 22 parts; 4 parts of hydroxyethyl acrylate; 8 parts of vinyl acetate; 6 parts of acrylic acid; 9 parts of montmorillonite; 1 part of magnesium chloride; 0.2 parts of initiator.
[0033] The mass ratio of epichlorohydrin to magnesium chloride is 3.0:1.
[0034] Table 1 Amount of raw materials used in the glue solutions of Examples 1 to 4 (parts by mass)
[0035] The high temperature resistance, 180° peeling force and electrolyte resistance of the high temperature resistant pressure sensitive adhesives prepared in Examples 1 to 4 and Comparative Examples 1 and 2 were tested respectively, and the specific data are shown in Table 2. The electrolyte resistance is tested by immersing the sample in electrolyte and then testing the 180° peeling force in accordance with GB / 2792-2014, and the specific method is as follows: the sample is cut into 20 mm*100 mm strips, immersed in electrolyte, and aged at 85°C for 4 hours; after the electrolyte is volatilized at room temperature for 30 minutes, a hot press is used to press at 85°C and 1 MPa for 38 minutes; and the peeling force after immersion in electrolyte is tested.
[0036] Table 2 Performance test data of the pressure-sensitive adhesives obtained in Examples 1 to 4 and Comparative Examples 1 and 2
[0037] Combining Table 1 and Table 2, it can be seen that the high temperature resistant pressure sensitive adhesive prepared by the present invention introduces magnesium chloride to catalyze the cross-linking reaction of the monomer in the middle of montmorillonite by intercalation. On the one hand, from the overall point of view, the degree of cross-linking around the montmorillonite system becomes larger while further realizing the intercalation of montmorillonite, the cohesive force of the pressure sensitive adhesive increases, and at the same time, the mobility of the chain segments in the pressure sensitive adhesive is guaranteed, and the wetting ability of the chain segments on the surface of the adherend is also maintained; on the other hand, the layered structure further dispersed by the cross-linking reaction enhances the mechanical properties and barrier properties of the pressure sensitive adhesive, hinders the transmission of the electrolyte in the pressure sensitive adhesive layer, and also inhibits the swelling behavior of the polymer in the pressure sensitive adhesive, so the loss of peeling force before and after the electrolyte infiltration is small. Therefore, the high temperature resistant pressure sensitive adhesive prepared by the present invention can be applied to the production of lithium ion batteries.
Claims
1. A method for preparing a high temperature resistant pressure sensitive adhesive, characterized in that: The following steps are involved: S1, isooctyl acrylate, butyl acrylate, hydroxyethyl acrylate, vinyl acetate, acrylic acid and montmorillonite loaded with magnesium chloride are uniformly mixed, and then an initiator is added in two batches to perform a cross-linking reaction to obtain a glue solution; The interlayer crosslinking reaction of isooctyl acrylate, butyl acrylate, hydroxyethyl acrylate, vinyl acetate and acrylic acid in montmorillonite; the initiator is AIBN; S2. The glue solution obtained in S1 is adjusted to have a solid content of 30% to 40% using ethyl acetate, a curing agent is added, the mixture is coated, cured, and attached to PET to obtain a high temperature resistant pressure sensitive adhesive.
2. The preparation method according to claim 1, characterized in that: The cross-linking in S1 includes the following steps: S11, after the monomers are mixed evenly, they are mixed with ethyl acetate solvent and transferred to a four-necked flask, half of the total amount of initiator is added and gradually heated to 85°C, and when reflux occurs on the condenser, the reaction is continued for 1 hour; S12, adding the remaining monomers, solvent and 1 / 4 of the total amount of initiator evenly into the reaction system within 2 hours, and then keeping the temperature to react for 1 hour; S13, adding the remaining initiator evenly into the reaction system within 0.5 h, and then keeping the temperature to react for 1.5 h; S14, cooling to obtain glue solution.
3. The preparation method according to claim 1, characterized in that: The preparation method of montmorillonite-loaded magnesium chloride comprises the following steps: S221, under nitrogen protection, add anhydrous magnesium chloride and ethanol into the flask, stir at 400r / min, the reaction temperature is 80°C, and react for 1 hour; S222, adding silanized montmorillonite to the flask, and continuing the reaction for 1 hour; S223, epichlorohydrin is added to the reaction system, and the reaction is stopped after 30 to 40 minutes. The mixture is allowed to stand, and the upper liquid is removed. The solid product is washed three times with n-hexane, and dried with nitrogen to obtain magnesium chloride supported by montmorillonite.
4. The preparation method according to claim 3, characterized in that: Polyvinyl pyrrolidone is also added in step S221, and the mass ratio of polyvinyl pyrrolidone to magnesium chloride is (0.5% to 0.8%):
1.
5. The preparation method according to claim 3, characterized in that: The method for preparing silanized montmorillonite comprises the following steps: S211, adding montmorillonite and sodium hexametaphosphate to distilled water for dispersion; S212, γ-aminopropyltriethoxysilane was stirred at room temperature in a H2O / ethanol system, and the montmorillonite suspension dispersed in S211 was dropped into it, refluxed with stirring, filtered, and the filter cake was dried at 120°C for 15 hours to obtain silanized montmorillonite.
6. The preparation method according to claim 5, characterized in that: The volume ratio of H2O to ethanol in the H2O / ethanol system in S212 is 1:
100.
7. The preparation method according to claim 3, characterized in that: The mass ratio of silanized montmorillonite to anhydrous magnesium chloride is (7 to 10):
1.
8. The preparation method according to claim 3, characterized in that: The mass ratio of epichlorohydrin to magnesium chloride is (2.5 to 3.5):
1.
9. The preparation method according to claim 1, characterized in that: The raw materials used for the cross-linking reaction include the following substances in parts by mass: 40 to 50 parts of isooctyl acrylate; 18 to 25 parts of butyl acrylate; 4 to 8 parts of hydroxyethyl acrylate; 6 to 12 parts of vinyl acetate; Acrylic acid 4 to 8 parts; 10 to 15 parts of montmorillonite loaded with magnesium chloride; Initiator 0.2 to 0.4 parts.
10. The preparation method according to claim 1, characterized in that: The curing temperature is 110°C to 120°C.